2015
DOI: 10.1007/s00276-015-1446-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple anatomical variations of the renal vessels associated with malrotated and unrotated kidneys: a case report

Abstract: Variations in the number of renal vessels represent the most common anatomical variations in renal vasculature. Here, a rare case of multiple anatomical variations of renal vessels was found in a 70-year-old female cadaveric dissection. Three renal arteries and two renal veins were observed to supply the right kidney, which was malrotated and ectopic; on the left side, the kidney was unrotated and presented two renal arteries and normal renal vein. In particular, we paid attention to the pattern of the three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Anatomical variations of renal arteries and veins are often reported in several studies [5,6,9,10], as well as case reports of duplicity and triplicity [12][13][14][15][16]. In the present study there were found triple renal arteries on the left kidney and double renal veins on the right kidney.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Anatomical variations of renal arteries and veins are often reported in several studies [5,6,9,10], as well as case reports of duplicity and triplicity [12][13][14][15][16]. In the present study there were found triple renal arteries on the left kidney and double renal veins on the right kidney.…”
Section: Discussionsupporting
confidence: 68%
“…The anatomical variations on the number of renal vessels are relatively common occurrences, being divided as unilateral and bilateral [5]. The presence of more than one renal artery has been the most common variation found [6,7].…”
Section: Discussionmentioning
confidence: 99%